The FBI and religion: faith and national security before and after 9/11 - Johnson, Sylvester A.; Weitzman, Steven (University of California Press, 2017)
Introduction "true faith and allegiance" : religion and the FBI / Sylvester A. Johnson and Steven Weitzman -- American religion and the rise of internal security : a prologue / Kathryn Gin Lum and Lerone Martin -- "If God be for you, who can be against you?" : persecution and vindication of the Church of God in Christ during World War I / Theodore Kornweibel, Jr. -- The FBI and the Moorish Science Temple of America, 1926-1960 / Sylvester A. Johnson -- J. Edgar Hoover, the FBI, and the religious cold war / Dianne Kirby -- Apostles of deceit : ecumenism, fundamentalism, surveillance, and the contested loyalties of Protestant clergy during the Cold War / Michael McVicar -- The FBI and the Catholic Church / Regin Schmidt -- Hoover's Judeo-Christians : Jews, religion, and Communism in the Cold War / Sarah Imhoff -- Policing public morality : Hoover's FBI, obscenity, and homosexuality -- The FBI and the Nation of Islam / Karl Evanzz -- Dreams and shadows : Martin Luther King Jr., the FBI, and the Southern Christian Leadership Conference / Sylvester A. Johnson -- A vast infiltration : Mormonism and the FBI / Matthew Bowman -- The FBI's "cult war" against the Branch Davidians / Catherine Wessinger -- The FBI and American Muslims after September 11 / Michael Barkun -- Policing Kashmiri Brooklyn / Junaid Rana -- Allies against Armageddon? : the FBI and the academic study of religion / Steven Weitzman